Biodegradable pH-responsive hydrogels for controlled dual-drug release. Issue 3 (5th January 2018) - Xu, Liang; Qiu, Linzi; Sheng, Yang; Sun, Yixin; Deng, Linhong; Li, Xinqing; Bradley, Mark; Zhang, Rong
Abstract : pH-Responsive biodegradable hydrogels based on NIPAM/AA and a PLLA/PEG macro-crosslinker demonstrated pH mediated differential release of doxorubicin and tetracycline. Abstract : Dual-drug loaded pH-responsive hydrogels were prepared as a delivery system carrying, as exemplars, both anti-cancer and anti-bacterial agents for pH controlled drug release. The hydrogels were composed of poly(l -lactide)- co -polyethyleneglycol- co -poly(l -lactide) dimethacrylates (with various molecular weights ofl -lactide oligomers) as a macromolecular crosslinker and copolymerized with acrylic acid and N -isopropylacrylamide. The biodegradability, biocompatibility and mechanical properties of the hydrogels were characterized with the hydrogels being nontoxic to cells, while showing a reversible >80% reduction in volume at pH 1.2 compared to pH 7.4. Drug release profiles showed differential release of tetracycline over doxorubicin at pH 1.2, with both drugs being released equally at pH 7.4. Biodegradability was tunable by altering the crosslinking density and pH, with the total degradation of the best gels observed within 2 weeks at pH 7.4.